PENGARUH TEKNIK LINE ART DALAM MENINGKATKAN KREATIVITAS MENGGAMBAR RAGAM HIAS GEOMETRIS SISWA KELAS V SDN 101764 BANDAR KLIPPA - Sry Hafiza Hasibuan; Putra Afriadi; Elvi Mailani; Winara; Sri Mustika Aulia (STKIP Subang, 2026)
This study aims to determine the effect of applying line art techniques on improving creativity in drawing geometric decorative motifs among fifth-grade students at SDN 101764 Bandar Klippa. This study used a quantitative approach with a true experimental design using a pretest-posttest control group design. The study population consisted of 47 students, with a sample of 32 students, consisting of 16 students in the experimental class and 16 students in the control class, selected through random sampling. Data collection techniques used observation sheets, interviews, and a creativity assessment rubric. Data analysis was conducted through normality and homogeneity tests, and hypothesis testing using the Independent Sample T-Test with SPSS. The results showed that the average post-test score in the experimental class was 65.94, higher than the average score in the control class (61.50). Furthermore, the results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.044 < 0.05, thus H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the application of line art techniques significantly improves students' creativity in drawing geometric decorative motifs. The application of line art techniques has been proven to enhance aspects of students' creativity, including fluency of ideas, flexibility, originality, and detail in drawing. Therefore, line art techniques can be used as an effective alternative learning method to enhance student creativity in fine arts lessons in elementary schools.